Filosofia, Política e Democracia na obra tardia de Richard Rorty - Silva, Marcelo de Almeida (2016)
This research thematizes the relationship between philosophy, politics and democracy in the work of Richard Rorty. More specifically, discusses its proposals to qualify the offers of philosophical production to the advancement of democratic practices. This will be done through the analysis of texts belonging to his last two decades of life, when his interest in politics became increasingly evident. In a scenario in which many claim that the resources offered by philosophy in its traditional conception as the search of unconditional truth, are no longer politically relevant, our goal here is to present the alternative of pragmatic political philosophy of Rorty and the main objections to this, showing how it can be useful to address the complexity of the political and social problems typical of democracies.